2012
DOI: 10.1080/02772248.2012.693492
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of selected metals in chicken eggs from commercial farms in Southern Nigeria

Abstract: This work presents the results of the determination of concentrations of the trace metals Ni, Zn, Mn, Pb, Cd, Cr, Co, Cu, and Fe in eggs from farms in Southern Nigeria. The mean concentrations (mg g À1 fresh weight) ranged from 0.6 to 1.2 for Ni, 3.1 to 8.9 for Zn, 0.45 to 0.65 for Mn, 0.4 to 1.2 for Pb, <0.09 to 0.3 for Cr, 0.1 to 0.3 for Cd, 0.26 to 0.34 for Co, 0.9 to 1.2 for Cu and 19.5 to 24.0 for Fe. The concentrations and estimated dietary intakes of these metals were below the respective statutory limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The high levels of Pb and Cd in the egg samples may be due to natural contamination through feeds or metal contamination in water in their habitat, with food being the primary source of Pb and Cd for humans and animals [101]. The mean levels of Cd and Hg in home-grown eggs/commercial eggs (0.016 and 0.007 mg/kg for Cd; 0.065 and 0.086 mg/kg for Hg, respectively) are more in line with those reported by some authors [10,26] and below those reported by other authors [91,[102][103][104].…”
Section: Elemental Determinationssupporting
confidence: 78%
“…The high levels of Pb and Cd in the egg samples may be due to natural contamination through feeds or metal contamination in water in their habitat, with food being the primary source of Pb and Cd for humans and animals [101]. The mean levels of Cd and Hg in home-grown eggs/commercial eggs (0.016 and 0.007 mg/kg for Cd; 0.065 and 0.086 mg/kg for Hg, respectively) are more in line with those reported by some authors [10,26] and below those reported by other authors [91,[102][103][104].…”
Section: Elemental Determinationssupporting
confidence: 78%
“…Concentrations of Ni in 180 eggs from farms in Southern Nigeria ranged from 0.01 to 2.06 mg/kg (mean of 0.86 mg/kg) (Iwegbue et al, 2012). The Ni ranges in 24 samples of commonly consumed food crops and in 12 fruits were < 0.001 (LOD)-3.13 mg/kg and < 0.001-1.76 mg/kg, respectively (Orisakwe et al, 2012).…”
Section: Nickel In Foodmentioning
confidence: 99%
“…Others, including As, Cd, Cr, Hg, Pb, and Sn, have no known essential function in living organisms and are toxic even at low concentrations. Heavy metals can cause serious adverse health effects in humans; thus, they are known as the most dangerous pollutants (2)(3)(4)(5)(6). Surface and groundwater resources are important for human life and for economic development (1).…”
Section: Introductionmentioning
confidence: 99%